Corrosion reduces wet abrasive wear of structural steel. (October 2015) - Liu, Yueting; Mol, J.M.C.; Janssen, G.C.A.M.
Abstract: Abrasive corrosive wear of materials is a phenomenon with great economical consequences. Here we present abrasive corrosive wear experiments performed on structural steel. We compare pin on disc experiments in artificial seawater, deionized water and ethanol. Counterintuitively the wear is observed to be smallest in seawater. We ascribe this result to the combined chemical modification of the steel surface due to local electrochemical interaction with the seawater and the mechanical interaction between the pin and the surface.